2016
DOI: 10.1111/imj.13055
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of exertional rhabdomyolysis following high‐intensity resistance training

Abstract: ER resulting from HIRT appears to have a benign course compared with rhabdomyolysis of other aetiologies in patients with a serum CK greater than 25 000 units/L. Conservative management of ER appears to be adequate, although this requires confirmation in future prospective studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 22 publications
2
11
0
Order By: Relevance
“…Several injury-related factors were observed in CrossFit practitioners and athletes. The most present factors within the studies were the type of exercise performed, in 5 studies 3,[22][23][24][25] , and the training time of CrossFit, in 3 studies 6,26,27 . In addition, sex presented relation to the prevalence of injuries, where men presented a higher number of injuries in relation to women, and the presence of prior injury was associated with new injuries.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several injury-related factors were observed in CrossFit practitioners and athletes. The most present factors within the studies were the type of exercise performed, in 5 studies 3,[22][23][24][25] , and the training time of CrossFit, in 3 studies 6,26,27 . In addition, sex presented relation to the prevalence of injuries, where men presented a higher number of injuries in relation to women, and the presence of prior injury was associated with new injuries.…”
Section: Resultsmentioning
confidence: 99%
“…Previously cited in the literature as a risk during the practice of CrossFit 10 , cases of rhabdomyolysis were reported in one related study 24 . According to Hak et al 21 , this may have occurred due to the inclusion of practitioners of various fitness levels, where rhabdomyolysis is to be expected in those who exercise in extremely high levels of intensity.…”
Section: Body Regions Affected and Type Of Exercisementioning
confidence: 96%
“…Due to some previous reporting of exercise-induced rhabdomyolysis [10,24], the following question was used to investigate incidence of the condition: "Were you in the period you participated in the CrossFit program medically diagnosed with Rhabdomyolysis? "…”
Section: Rhabdomyolysismentioning
confidence: 99%
“…A retrospective cross-sectional study of patients presenting with rhabdomyolysis during a period of 12 months in 2013 and 2014 at two tertiary referral hospitals in Melbourne, Australia, reported that 12 of 34 cases of rhabdomyolysis wereexertional in origin. Of these 12 cases, 5were reported to be caused by CrossFit [24]. Another retrospective cohort study found that of 523 patients presented with injuries associated with CrossFit activities.…”
Section: Exertional Rhabdomyolysismentioning
confidence: 99%
“…If these enzymes remain elevated, the integrity of the muscle cell is not restored. So, new training session is not recommended, especially for athletes that use strength and power in their sports because CK elevation has been associated with a failure of rhabdomyolysis treatment (Huynh et al, 2016).…”
Section: Introductionmentioning
confidence: 99%